(untitled) (Computer systems and information technologies, 2022)
The aim of this paper is creating some ternary elements. The threshold element of ternary logic on bipolar transistors and elements of ternary systems based on it are considered. The main disadvantages of this approach are identified. The multi-threshold element of multivalued logic and its specific four-threshold implementation are considered. The scientific nowelty is the using of a multithreshold element of multivalued logic as a basis for constructing elements of ternary systems. It is shown that the advantages of a multi-threshold element of multi-valued logic are a larger number of thresholds of input signals, a larger number of levels that it can distinguish and a larger number of output signals. The implementation of some ternary elements, such as half-adder, disjunction and strong conjunction, is given. The practical significance of obtained results is that the multithreshold element of multivalued logic allows us to use it for synthesis basic elements of ternary logic and use one approach for all of them. Additional practical advantage is that in practice it allows you to build more diverse logical and arithmetic devices with a simplified implementation. The implementation of ternary devices based on threshold logic is a way to create ternary devices that can compete with binary devices in terms of equipment, capacity, operational capabilities, and variety. This, in turn, leads to greater speed and simplification of the structure of devices, as well as increasing the speed of data processing. These advantages are significant in such areas of computer use as intelligent data processing systems, expert systems, decision theory, i.e., where data analysis is performed. Prospects for further research are to use the method of construction and synthesis of nodes of ternary computer systems, based on MTEML. Their optimization, and development of principles of mathematical modeling and software of such systems and their elements is expedient.